A QUALITATIVE STUDY ON THE IMPACT OF THE DEATH PENALTY ON THE PREVENTION OF CORRUPTION CRIMES IN INDONESIA - Noldy Sondakh; Yohanes Karundeng; Rivka Lumowa; Ferdinand Rantung; Meiske Pangemanan (CV. Tirta Pustaka Press, 2026)
Corruption is classified as an extraordinary crime due to its widespread impact on governance systems, the national economy, and public trust in Indonesia. Various efforts have been undertaken to combat corruption, including the discourse on applying the death penalty as the maximum sanction for severe corruption offenses. This study aims to analyze the effectiveness of the death penalty in preventing major corruption cases in Indonesia using a qualitative case study approach. Data were collected through in-depth interviews with selected key informants based on relevant expertise and supported by document analysis of applicable legal regulations and policy reports. This study concludes that the death penalty cannot stand alone as an anti-corruption measure but must be integrated into a broader, systemic strategy that combines both punitive and preventive approaches in a balanced and effective manner. Factors such as the integrity of the judicial system, the risk of miscarriages of justice, and social legitimacy are critical in determining the success of such a policy. Furthermore, public perception of the death penalty is deeply influenced by religious, cultural, and ethical values. This study concludes that the death penalty cannot stand alone as an anti-corruption measure but must be integrated into a broader, systemic strategy that combines both punitive and preventive approaches in a balanced and effective manner.